South Asian regional cooperation : a socio-economic approach to peace and stability - Hafiz, M. Abdul; Iftekharuzzaman; Bangladesh Institute of International and Strategic Studies; International Conference on South Asian Regional Cooperation (1985 : Dhaka, Bangladesh) (Dhaka : Bangladesh Institute of International and Strategic Studies, 1985)
Papers presented at an International Conference on South Asian Regional Cooperation, held at Dhaka, January 14-16, 1985, under the aegis of the Bangladesh Institute of International and Strategic Studies.
Includes bibliographies and index.
Keywords: Regionalism -- South Asia -- Congresses; South Asian cooperation -- Congresses; South Asia -- Economic policy -- Congresses; South Asia -- Politics and government -- Congresses; South Asia -- Social policy -- Congresses